A normative reference vs. baseline testing compromise for ImPACT: the CARE consortium multiple variable prediction (CARE-MVP) norms - Asken, B. M.; Houck, Z. M.; Schmidt, J. D.; Bauer, R. M.; Broglio, S. P.; McCrea, M. A.; McAllister, T. W.; Clugston, J. R. (Sports Medicine, 2020)
Background: Sports medicine clinicians routinely use computerized neurocognitive testing in sport-related concussion management programs. Debates continue regarding the appropriateness of normative reference comparisons versus obtaining individual baseline assessments, particularly for populations with greater likelihood of having below- or above-average cognitive abilities. Improving normative reference methods could offer alternatives to perceived logistical and financial burdens imposed by universal baseline testing. Objectives: To develop and validate the Concussion Assessment, Research, and Education (CARE) Consortium Multiple Variable Prediction (MVP) norms for the Immediate Postconcussion Assessment and Cognitive Testing (ImPACT). Methods: We developed the CARE-MVP norms for ImPACT composite scores using regression-based equations. Predictor variables included sex, race (white/Caucasian, black/African American, Asian, or Multiple Races), medical history [attention-deficit/hyperactivity disorder (ADHD), learning disorder (LD), prior concussion(s), prior psychiatric diagnosis], and an estimate of premorbid intellect (Wechsler Test of Adult Reading). CARE-MVP norms were first validated in an independent sample of healthy collegiate athletes by comparing predicted and actual baseline test scores using independent-samples t-tests and Cohen`s d effect sizes. We then evaluated base rates of low scores in athletes self-reporting ADHD/LD (vs. non-ADHD/LD) and black/African American race (vs. white/Caucasian) across multiple normative reference methods (Chi square, Cramer`s V effect size). Lastly, we validated the CARE-MVP norms in a concussed sample (dependent samples t test, Cohen`s d effect size). Results: A total of 5233 collegiate athletes (18.8 ± 1.2 years, 70.5% white/Caucasian, 39.1% female) contributed to the CARE-MVP norms (development N = 2616; internal validation N = 2617). Race and WTAR score were the strongest and most consistent ImPACT score predictors. There were negligible mean differences between observed and predicted (CARE-MVP) baseline scores (Cohen`s d < 0.1) for all ImPACT composite scores except Reaction Time (predicted ~ 20 ms faster than observed, d = - 0.28). Low score base rates were similar for athletes across subpopulations when using CARE-MVP norms (ADHD/LD, V = 0.017-0.028; black/African American, V = 0.043-0.053); while, other normative reference methods resulted in disproportionately higher rates of low scores (ADHD/LD, V = 0.062-0.101; black/African American race, V = 0.163-0.221). Acute (24-48 h) postconcussion ImPACT scores were significantly worse than CARE-MVP norms but notably varied as a function of concussion symptom severity. Conclusions: Results support CARE-MVP norm use in populations typically underrepresented or not adjusted for in traditional normative reference samples, such as those self-reporting ADHD/LD or black/African American race. CARE-MVP norms improve upon prior normative methods and may offer a practical, simple alternative for collegiate institutions concerned about logistical and financial burden associated with baseline testing. An automated scoring program is provided.